Dual salt bridges govern proton gating and calcium leak in Bs YetJ across bilayers and live cells - Chu-Chun Cheng; Chieh-Chin Li; Yun-Shan Wang; Chun-Wei Lin; Yun-Wei Chiang (Proceedings of the National Academy of Sciences, 2026)
Proton-coupled ion transport is a fundamental chemical process underlying membrane physiology, yet how local electrostatics are transduced into gated Ca 2+ permeation remains poorly defined. Here, we combine single-channel planar bilayer electrophysiology, nanodisc-based double electron–electron resonance spectroscopy, atomistic modeling, and a nanodisc nano-delivery strategy that enables direct functional insertion of purified membrane proteins into live mammalian cells. Applying this integrated toolkit to the bacterial transmembrane Bax-inhibitor-1–containing motif prototype Bs YetJ, we resolve a hierarchical electrostatic gating mechanism governed by two salt bridges with distinct physical roles. A periplasmic E49–R205 interaction functions as a proton-sensitive latch that drives transmembrane helix 2 displacement and controls opening probability, while a cytoplasmic E182–R15 pair operates as a local electrostatic determinant of Ca 2+ self-block that tunes conductance and selectivity without large-scale conformational change. Quantitative separation of these effects reveals how protonation reshapes the energy landscape of ion permeation. Live-cell Ca 2+ imaging following nano-delivery recapitulates this gating logic in a cellular membrane setting. Together, this work establishes dual salt-bridge electrostatics as a chemical principle for graded Ca 2+ leak and introduces nano-delivery as a powerful platform for connecting molecular electrostatics to cellular ion transport.